The effect of promoters in La0.9M0.1Ni0.5Fe0.5O3 (M = Sr, Ca) perovskite catalysts on dry reforming of methane - Yang, Eun-hyeok; Noh, Young-su; Ramesh, S.; Lim, Sung Soo; Moon, Dong Ju (ELSEVIER SCIENCE BV, 2015)
Nickel-based catalysts are typically used for syngas production via reforming reactions. The reforming of methane using carbon dioxide, called dry reforming of methane (DRM), is an effective way to produce syngas from these two notable greenhouse gases. However, Ni-based catalysts used for DRM undergo severe coke deposition. In the current study, perovskite-type oxide catalysts were prepared using the modified EDTA-cellulose method and characterized by the N-2 physisorption, TPR, CO2-TPD, XRD, TGA, SEM and TEM-EDX techniques. The influence of partial substitution of La by Sr/Ca was investigated in the dry reforming reaction for the production of synthesis gas, and the basicity of the catalysts was varied by substituting the A site with either Sr or Ca, which modified the catalytic activity under the tested conditions. It was found that the perovskite catalysts demonstrated superior carbon resistance during the reaction, with La0.9Ca0.1Ni0.5Fe0.5O3 catalyst exhibiting the best catalytic performance among the prepared perovskite catalysts. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: SYNTHESIS GAS; CARBON-DIOXIDE; NICKEL-CATALYSTS; CO2; STEAM; CH4; LA; FE; CONVERSION; TOLUENE